Students’ understanding of genetics through blended learning activities - Santiago, Jacklyn C. (Animo Repository, 2017)
This action research explored the effect of blended learning activities on students’ understanding of Genetics concepts. It involved eighty-one (81) 2nd year high school students of Canossa School of Sta. Rosa, Laguna, Philippines. The researcher-made teaching and learning plan on Genetics included blended learning activities, where face-to-face instruction in the classroom was enriched with online learning activities. The blended learning activities used GENYO as the online learning platform. A Genetics Concept Test was administered both as a pretest and a posttest to examine the students’ level of conceptual understanding before and after exposure to blended learning activities. Findings in this study revealed significant differences in the pretest and posttest scores of the students (t =−16.007, p = 0.000) and students test scores posted a moderate normalized gain (g = 0.45). Evidently, blended learning facilitated students’ understanding of Genetics concepts. Results were suggestive that employing blended learning allow and encourage the students to make use of computers in learning, a practice that will reinforce students’ positive attitude towards computer and promote computer self efficacy. Science educators should also be advocates of technology that encourage the use of other modern gadgets, such as tablets and smartphones, as instruments for learning. © 2017 American Scientific Publishers All rights reserved.